Modificações na casca de arroz para a adsorção de azul de metileno em batelada e leito fixo - Franco, Dison Stracke Pfingsten (2016)
In this work, rice husk and its modifications were investigated as methylene blue adsorbents, using discontinuous (batch) and continuous (fixed bed) adsorption operations. The rice husk was modified through alternative treatments like; supercritical extraction with CO2, assisted ultrasound and sodium hydroxide attacks. The adsorbents were characterized through Fourier transform infrared spectroscopy (FTIR), x-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive x-ray spectroscopy (EDS). For the batch adsorption, Langmuir and Hill models were used to describe the isotherms. From the thermodynamic perspective the adsorption was spontaneous and the adsorption capacity increases with the temperature increase. The fixed bed adsorption was optimized and adsorbents were applied in the optimal condition, then dynamic models (Thomas, BDST, Yoon-Nelson) were fitted to the experimental data to represent the breakthrough curve. In general it was found that the treatments enhanced the adsorption capacity for both process. For the batch process a pattern indicating that the NaOH rice husk (65.0 ±0.4 mg g-1) was superior to UA (58.7 ±2,1 mg g-1), SCO2 (56.4 ±0.6 mg g-1) and raw rice husk (52.2 ±1.3 mg g-1) was observed. For the fixed, the same behavior was found. The breakthrough time for the optimal conditions were 109, 240, 155 and 385 min for raw rice husk, rice husk treated with assisted ultrasound, supercritical CO2 and NaOH respectively.